Bio-rational management packages of jassid and shoot and fruit borer of okra (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted for bio-rational management of jassid (Amrasca biguttula biguttula), and shoot and fruit borer of okra (Earias vittella) at experimental field of Bangladesh Agricultural Research Institute (BARI) during April to July 2016. Management Packages used in this study were package 1: Hand picking+ pheromone mass trapping for Earias vittella + spraying of bio-neem plus 1 EC @ 1ml l-1 of water, package 2: Hand picking + pheromone mass trapping for Earias vittella + spraying of emamectin benzoate 5 SG @ 1g l-1 of water, package 3: Hand picking + pheromone mass trapping for Earias vittella + spraying of spinosad 45 SC @ 0.4ml l-1 of water, package 4: Farmers practice: Spraying of cypermethrin 10 EC@ 1ml l-1 of water at seven days interval, and an untreated control. Among the packages bio-neem based one (Package 1) was the best to control jassid population, emamectin benzoate based package (Package 2) was the best to control okra shoot and fruit borer infestation on shoot and spinosad based package (Package 3) was the best to control okra shoot and fruit borer infestation on fruit. Statistically similar yields were obtained from bio-rational package treated plots and their yields were significantly higher than farmer’s practice (Package 4) and untreated control plot. Higher benefit cost ratio (4.57-9.18) was obtained from bio-rational management package treated plots compare to that of farmer’s practice plot (4.50).Bangladesh J. Agril. Res. 43(2): 323-332, June 2018